Telaah Integratif Filsafat Hukum Publik dan Teori Maslahah terhadap Kebijakan Amnesti Pajak di Indonesia - Khasanah, Karimatul (Fakultas Syariah IAIN Purwokerto, 2021)
Tax amnesty policy has been issued by the Government of Indonesia for six times, i.e., 1964, 1984, 2007, 2009, 2015, and 2016. But actually, such policy is not a common one, because taxes are obligation for everyone who has met the criteria as a taxpayer. Therefore, the emergence of this policy often leads to controversial responses from many people. This research aims to reveal how the analysis of the philosophy of public law (justice, expediency and legal certainty) toward tax amnesty policies in Indonesia, which is integrated with the theory of maÃ¡Â¹Â£laÃ¡Â¸Â¥ah (public benefit) in Islamic legal philosophy (Usul al-Fiqh). The findings of this study indicate that the implementation of the three legal principles in the tax amnesty policy in Indonesia actually has a legal legitimacy (iÃ¢â‚¬â„¢tibÃ„Âr syarÃ¢â‚¬â„¢iy) in the perspective of maÃ¡Â¹Â£laÃ¡Â¸Â¥ah (public benefits). As the character of the maslahah, then the hierarchy of the three is tentative depending on the level of urgency driven by surronding situations and conditions.